On the identities of Callianassa bouvieri Nobili, 1904, C. maldivensis Borradaile, 1904, and C. gravieri Nobili, 1905 (Crustacea: Decapoda: Callianassidae): a morphometric approach. Zootaxa 3049: 39–56 (Erratum) - Dworschak, P. C. (Zootaxa, 2012)
Erratum